Gambaran Hasil Pengetahuan Sasaran Kegiatan Edukasi Pentingnya Menjaga Diri Bagi Remaja Guna Mencegah Pernikahan Dini di Mts Fatahilah Kota Cimahi - Ivan Tanoto; Novis Safitri; Nurfitriyatul Aini; Tasya Mutiara Hendryana; Dinda Lestari; Syavira Damayanti; Nurlaela Hamidah; Novialita Vandanu; Dimas Galeng Jatigiri; Fadila Imanda; Sri Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2024)
This education on preventing early marriage is part of the implementation of the 2023 BKKBN Thematic KKN program which aims to create a community movement aware of stunting and to increase teenagers' knowledge about the factors and risks and increase knowledge about early marriage. The method for implementing this activity uses a face-to-face seminar method, followed by a discussion and question and answer session. There were 50 participants in this activity, consisting of 27 male students and 23 female students from class IX MTs Fatahillah. The results of this activity showed that based on the results of the pretest and pos test scoring, there was an increase in the average score, and based on interviews and observations, all participants were very enthusiastic and expressed that this educational activity really added new knowledge to them.